AN INTEGRATED APPROACH TO THE ANALYSIS OF RELIABILITY OF MACHINE-BUILDING ENTERPRISES IN THE INDUSTRY ENVIRONMENT - N. Arsenieva; L. Putyatina; A. Zheltenkov (Вестник университета)
The purpose of the article is to describe methodological approaches to the complex concept of reliability of engineering enterprises in a competitive environment. The concept of enterprise reliability is proposed to include the following areas of analysis: sustainability of economic growth, financial stability, industrial mobility and market stability. Each of the areas under consideration has its own aspects of analysis and indicators. The definitions of the proposed directions have been given, the need for their joint use in determining the reliability of the enterprise has been substantiated. The main content of the study is to analyze each component of the reliability of the enterprise, the proposed system of indicators that determine them, as well as the most favorable trends in the last time to improve the status and reliability of the enterprise. According to the results of the conducted research, the conclusion about the necessity of development of methods of reliability evaluation of engineering enterprises through the levels to create the structure of sectoral development opportunities has been made.